Growth and oscillation theory of solutions of some linear differential equations - Belaıdi, Benharrat (Mat. Vesnik, 2008)
The basic idea of this paper is to consider fixed points of solutions of the differential equation f(k) + A(z) f = 0, k ¸ 2, where A(z) is a transcendental meromorphic function with ½ (A) = ½ > 0. Instead of looking at the zeros of f (z) ¡ z, we proceed to a slight generalization by considering zeros of f (z) ¡ ' (z), where ' is a meromorphic function of finite order, while the solution of respective differential equation is of infinite order.
Keywords: Linear differential equations; Meromorphic solutions; Hyper order; Exponent of convergence of the sequence of distinct zeros; Hyper exponent of convergence of the sequence of distinct zeros